Emerging hydrovoltaic technology. Issue 12 (December 2018) - Zhang, Zhuhua; Li, Xuemei; Yin, Jun; Xu, Ying; Fei, Wenwen; Xue, Minmin; Wang, Qin; Zhou, Jianxin; Guo, Wanlin
Abstract Water contains tremendous energy in a variety of forms, but very little of this energy has yet been harnessed. Nanostructured materials can generate electricity on interaction with water, a phenomenon that we term the hydrovoltaic effect, which potentially extends the technical capability of water energy harvesting and enables the creation of self-powered devices. In this Review, starting by describing fundamental properties of water and of water–solid interfaces, we discuss key aspects pertaining to water–carbon interactions and basic mechanisms of harvesting water energy with nanostructured materials. Experimental advances in generating electricity from water flows, waves, natural evaporation and moisture are then reviewed to show the correlations in their basic mechanisms and the potential for their integration towards harvesting energy from the water cycle. We further discuss potential device applications of hydrovoltaic technologies, analyse main challenges in improving the energy conversion efficiency and scaling up the output power, and suggest prospects for developments of the emerging technology. Recent progress on generating electricity from the direct interaction of carbon nanostructures with flowing, waving, dropping and evaporating water is summarized.